Challenges for Translator’s Education in the European Union - Kučiš, Vlasta (Array, 2011)
The paper will analyze the current situation in translation inside the European Union (EU) from the aspect of plurilingual and multicultural principles. Current linguistic strategy and policy in the EU institutions is complex. It consists currently of 27 member states, having 23 official languages, with the tendency of enlargement. Linguistic diversity and access the documentation in the proper language are fundamental principles, asking for everyday translation of considerable quantities of texts. Multilingualism, as one of the main features of the European society, becomes the challenge and the main motivation for the development of educational programs providing linguistic, cultural and technical knowledge, as well as language, organizational and technical skills for modern translator. European Master's in Translation (EMT), which is promoting a common, interdisciplinary education for translators with curriculum structure focused on theoretical research, practical exercises, skill development and use of translation tools. The paper analyzes the knowledge and skills that a modern-day European translator needs, as defined and proposed by the EMT educational programme.